2021
DOI: 10.3233/jad-210690
|View full text |Cite
|
Sign up to set email alerts
|

Single-Task or Dual-Task? Gait Assessment as a Potential Diagnostic Tool for Alzheimer’s Dementia

Abstract: Background: A person’s gait performance requires the integration of sensorimotor and cognitive systems. Therefore, a person’s gait may be influenced by concurrent cognitive load such as simultaneous talking. Although it has been known that gait performance of people with Alzheimer’s dementia (AD) is compromised when they attempt a dual-task walking task, it is unclear if using a dual-task gait performance during an AD assessment yields higher diagnostic accuracy. Objective: This study was designed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Dual-task walking is walking while performing another task that occupies cognitive resources, such as using mobile phones or talking. Compared with single-task walking, dual-task walking is more challenging, more common in daily life, and more conducive to the discovery of potential gait abnormalities in activities of daily living (ADL) ( Liang et al, 2019 ; Oh, 2021 ). Imaging studies have also shown that gait and cognitive control share a brain network, especially in the cognitive and motor zones of the frontal cortex ( Rosano et al, 2006 ; Annweiler et al, 2012 ; Montero-Odasso et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dual-task walking is walking while performing another task that occupies cognitive resources, such as using mobile phones or talking. Compared with single-task walking, dual-task walking is more challenging, more common in daily life, and more conducive to the discovery of potential gait abnormalities in activities of daily living (ADL) ( Liang et al, 2019 ; Oh, 2021 ). Imaging studies have also shown that gait and cognitive control share a brain network, especially in the cognitive and motor zones of the frontal cortex ( Rosano et al, 2006 ; Annweiler et al, 2012 ; Montero-Odasso et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between gait characteristics and disorientation has already been demonstrated in conditions such as delirium and dementia ( Arjunan et al, 2019 ; Evensen et al, 2019 ; Oh, 2021 ; Weizman et al, 2021 ). In contrast, the detection of disorientation events using gait and accelerometry features has been little explored.…”
Section: Discussionmentioning
confidence: 87%
“…Some of these real-world studies were primarily aimed at exploring different components of spatial orientation in normal human behavior and the underlying neural basis but did not aim to map the full range of navigational behavior in everyday situations ( Wei et al, 2020 ). Other studies mainly focused on the early detection of dementia symptoms using gait characteristics in real-world environments ( Mc Ardle et al, 2021 ; Mulas et al, 2021 ; Weizman et al, 2021 ) or under dual task conditions ( Oh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been suggested that motor-cognitive dual-task performance may be a more effective diagnostic tool than gait alone in people with dementia [20].…”
Section: Introductionmentioning
confidence: 99%